Clinical, radiographic and histological findings of seven teeth from two California sea lions (Zalophus californianus) housed under professional care - Nemec, Ana; Gracis, Margherita; Monreal-Pawlowsky, Tania; Magnone, William; Pritelli, Antonella; Bell, Cynthia (Frontiers in Veterinary Science, 2024)
Seven teeth extracted from two adult California sea lions (Zalophus californianus) due to pulp exposure and/or to gain access to the mandibular canine teeth were histologically evaluated and the findings compared to clinical and radiographic findings. Three teeth were diagnosed with pulp exposure and two of these showed no radiographic signs of endodontic disease and were histologically vital with prominent coronal pulpitis and a pulp polyp. Another tooth with pulp exposure was showing clinical and radiographic signs of endodontic disease and was histologically confirmed with pulp necrosis. A discoloured incisor tooth was showing radiographic signs of endodontic disease and was also histologically non-vital. Two clinically and radiographically healthy mandibular first premolar teeth and one second incisor tooth had no evidence of pulpitis or pulp necrosis, but had pulp canal obliteration Although extractions of affected teeth in California sea lions are considered the most practical and beneficial therapy, these are associated with the risks of extensive trauma and anaesthesia, and the need to perform these surgical procedures on-site under variable conditions. The fact that California sea lions can be trained to allow conscious dental radiographic re-checks, monitoring teeth with clinical signs of pulp polyp formation and without radiographic signs of endodontic disease warrant further evaluation/reconsideration from previous recommendations. Endodontic treatment of abscessed teeth in California sea lions is reportedly unsuccessful and is discouraged. However, vital pulpectomy could be an alternative treatment to extraction in teeth with pulp polyps as it was found to be highly successful in humans,.